2012
DOI: 10.1038/eye.2011.359
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Graves’ ophthalmopathy-specific quality of life in Korean patients

Abstract: Aim To investigate the clinical significance of Grave's ophthalmopathy-specific quality of life (GO-QOL) in Korean patients. Methods A cross-sectional study was conducted at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 12 publications
4
27
3
1
Order By: Relevance
“…The results of this survey in this group of patients from Argentina showed that GO has a significant impact on their lives, the majority of respondents reported limitation in daily activities such as reading and watching television, as well as impaired selfconfidence and changes in appearance; similar to those reported by other authors in other countries (7)(8)(9). However, we had 35.2% missing answers for driving and 28.2% for cycling.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results of this survey in this group of patients from Argentina showed that GO has a significant impact on their lives, the majority of respondents reported limitation in daily activities such as reading and watching television, as well as impaired selfconfidence and changes in appearance; similar to those reported by other authors in other countries (7)(8)(9). However, we had 35.2% missing answers for driving and 28.2% for cycling.…”
Section: Discussionsupporting
confidence: 62%
“…Choi and cols. (9) used the questionnaire among a Korean population and likewise found that the survey was associated with GO activity. Son and cols.…”
Section: Introductionmentioning
confidence: 99%
“…7 The GO-QOL is made up of two subscales: 'vision-related' and 'appearance-related' quality of life. 5 The GO-QOL has been found to be a valid and reliable disease-specific measure of quality of life with high internal consistency (α = 0.86 for the visual function scale and α = 0.82 for the appearance scale). 13 Subscale scores were calculated by following the questionnaire guidelines, 13 and higher scores on each subscale indicate better health-related quality of life.…”
Section: Clinical Measuresmentioning
confidence: 99%
“…4 There is also growing evidence that GO has a detrimental impact on vision-related daily functioning including reading, watching TV, and driving. [5][6][7] People with GO have been found to have a poorer quality of life than patients with other chronic conditions including diabetes, emphysema, and heart failure. 4,8 Although it is important to establish the impact GO may have on a patient's well-being, it is equally important to understand what factors explain how some people live within normal levels of mood and experience a better quality of life than others.…”
Section: Introductionmentioning
confidence: 99%
“…For more aggressive therapies, a change of at least 10 points is usually considered as the minimal clinically relevant difference (143). The GO-QoL has been validated in different populations (145,146,147,148) and translated into 15 different languages. For these reasons, QoL has become also suitable as an outcome measure of therapeutic response in RTC trials, and an improvement of GO-QoL has been shown in patients responsive to therapy.…”
Section: Measurement Of Qol In Gomentioning
confidence: 99%